ANALYZING THE CONSUMER PURCHASE INTENTION IN SELECTING MOTORCYCLE BRAND USING ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH - Walone, Lidya N.G. (Jurnal Berkala Ilmiah Efisiensi, 2016)
Currently, the transportation is becoming a very important to support all the human activities. Many people have private cars and motorcycles, however, the congestion created them to prefer a motorcycle as a daily transportation for the efficient and effective of their activities. This aims to determine which motorcycle brand that are chosen the most and which the criteria that are influence the most. This research used Analytical Hierarchy Process (AHP) to compare each motorcycle brand based on the criteria; product quality, performance, price, advertising, and sales Promotion. This research held from May-June 2016 in Manado City. 50 users of the three motorcycle brand were surveyed as samples. The results show that Product Quality is the most important criteria, followed by Performance, Price, Sales Promotion, and the last Advertising. In the best motorcycle brand result, Yamaha become the best motorcycle brand chosen by respondent, followed by Honda and Suzuki motorcycle.